2012
DOI: 10.1111/j.1600-0854.2012.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Isoform‐Selective Vps21/Rab5 Signaling at Endolysosomal Organelles by Msb3/Gyp3

Abstract: Traffic through endosomes and lysosomes is controlled by small G-proteins of the Rab5 and Rab7 families. Like humans, Saccharomyces cerevisiae has three Rab5s (Vps21, Ypt52, and Ypt53), and one Rab7 (Ypt7). Here, we elucidate the functional roles and regulation of the yeast Rab5s. Using GFP-tagged cargoes, a novel quantitative multivesicular body (MVB) sorting assay, and electron microscopy, we show that MVB biogenesis and cargo sorting are severely impaired in vps21Δ ypt52Δ double mutants. Ypt53, the third Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
98
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(111 citation statements)
references
References 78 publications
(128 reference statements)
12
98
1
Order By: Relevance
“…Separate from its activity as an Rsp5 client, trafficking of Cps1 from the cell membrane to the vacuole has been well characterized and Cps1 is frequently used as a model cargo to study protein trafficking through MVBs (Odorizzi et al ., 1998). Using a quantitative, luciferase‐based assay to search for defects in MVB formation and sorting (Nickerson et al ., 2012; Nickerson & Merz, 2015), we observed that the original chr5 disome has a Cps1 trafficking defect that is ameliorated by the deletion of BUL1 or the bul1 Q146K allele (Fig. 4).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…Separate from its activity as an Rsp5 client, trafficking of Cps1 from the cell membrane to the vacuole has been well characterized and Cps1 is frequently used as a model cargo to study protein trafficking through MVBs (Odorizzi et al ., 1998). Using a quantitative, luciferase‐based assay to search for defects in MVB formation and sorting (Nickerson et al ., 2012; Nickerson & Merz, 2015), we observed that the original chr5 disome has a Cps1 trafficking defect that is ameliorated by the deletion of BUL1 or the bul1 Q146K allele (Fig. 4).…”
Section: Resultsmentioning
confidence: 65%
“…See Nickerson et al . (2012) for details (unpaired, two‐tailed t ‐test, ** P  =   0.002, *** P  =   0.0002). Bars represent means ± SD of 4 biological replicates each.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The small GTPase, Rab5, is a key regulator of early endocytosis, being involved in targeting plasma membrane-derived endocytic vesicles to endosomes, fusion between early endosomes, MVB biogenesis and endosomal motility [14][15][16][17][18] . In addition to these traditional roles, it has recently been demonstrated that Rab5 has a role in maturation of the early to the late endosome [19][20][21] .…”
mentioning
confidence: 99%